GALA NIGHT 2016 SHOWCASING CULTURAL DIVERSITY ON CAMPUS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 24 November 2016 – Universiti Sains Malaysia (USM) International Week is a major event organised annually by the Postgraduate Students Association (PSA) and USM NonResident Students (PETAS). First organised by PSA and PETAS in 2005, this year marks the 11th edition of the endeavour in realising it to become an exciting event at USM.